Gestion intégrée des zones côtières et décentralisation - Mathieu Doat (VertigO)
It’s difficult to articulate the ICZM (Integrated Coastal Zone Management) with local politics because the area of the ICZM is taller than the territory of local politics.Moreover some rules between the two concepts are in conflict. In fact, local territories and proximities politics are the most efficient to regulate the coast.